The Influence of Business Intelligence Dashboard in Decision-Making Process: A Case Study in Government Agency - Arlinda Wibiayu; Manahan Siallagan (Budapest International Research and Critics University, 2022)
With the rapid development in big data and business intelligence platforms, the government is required to keep up with the technology in managing the organization's data to give excellent public service. The government as a policy maker should make policies and make a decision based on data rather than just the manager’s intuition. The investment in a business intelligence platform should ease in doing routine and simplify the decision-making process. The objective of this study is to know employee perception on the data visualization available in Indonesian FDA and list the possibilities to improve it. The data used are from primary and secondary data. The primary data get from employee surveys while secondary data is from company reports and other sources on the internet. The analysis using quantitative analysis with ANOVA. Data visualization using color can increase willingness to read and people can faster grab the sense from visuals. This will help a manager digest all the data to make a decision. After conducting the study, the result showed that a business intelligence dashboard could help the employee in providing a brief overview of real-time data in general when needed. The dashboard capability that the employee thinks important is data filtering. Having a business intelligence dashboard can help managers make the decision process faster and more precise.